Isolation and Characterization of Five Severe Acute Respiratory Syndrome Coronavirus 2 Strains of Different Clades and Lineages Circulating in Eastern India - Singh, Bharati; Avula, Kiran; Chatterjee, Sanchari; Datey, Ankita; Ghosh, Arup; De, Saikat; Keshry, Supriya Suman; Ghosh, Soumyajit; Suryawanshi, Amol Ratnakar; Dash, Rupesh; Senapati, Shantibhusan; Beuria, Tushar K.; et al. (Frontiers in Microbiology, 2022)
The emergence of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) as a serious pandemic has altered the global socioeconomic dynamics. The wide prevalence, high death counts, and rapid emergence of new variants urge for the establishment of research infrastructure to facilitate the rapid development of efficient therapeutic modalities and preventive measures. In agreement with this, SARS-CoV-2 strains were isolated from patient swab samples collected during the first COVID-19 wave in Odisha, India. The viral isolates were adapted to in vitro cultures and further characterized to identify strain-specific variations in viral growth characteristics. The neutralization susceptibility of viral isolates to vaccine-induced antibodies was determined using sera from individuals vaccinated in the Government-run vaccine drive in India. The major goal was to isolate and adapt SARS-CoV-2 viruses in cell culture with minimum modifications to facilitate research activities involved in the understanding of the molecular virology, host–virus interactions, drug discovery, and animal challenge models that eventually contribute toward the development of reliable therapeutics.